JEJAK KESULTANAN BANTEN DI LAMPUNG ABAD XVII (Analisis Prasasti Dalung Bojong) - Wijayati, Mufliha (Analisis: Jurnal Studi Keislaman, 2011)
Lampung is the pepper-producing  areas that had been under seizing of kingdoms of the surrunding since long time. The arrival of Islam in Lampung, in a lot of analysis, is also closely related to its existence as the pepper-producing  area. When the Port of XVI-XVII centuries Banten grown into an international center for trade with commodities and spices,  especially  pepper,  then  for the supply  of the pepper,  it later expanded into a number of pepper-producing  regions, including Lampung. A number of policies applied to pepper-producing  regions, including  tying a number  of rules in the population  with a charter granted to the representative  retainer  of Banten in the area, one of them in the context of Lampung is the Charter Dalung Bojong which is the object study of this article. Using archeological history approach, the  present  author  attempted  to  uncover  the  elements  contained in  the  inscription  as  historical  sources  that  provide  information about  the  events  of  political,  bureaucratic,  religious,  and  the  life of the community  in the past. It is revealed  that the charter  issued in  1102  H/1691  M  by  Sultan  Abul  Mahasin  Muhammad   Zainul Abidin  (1690-1733  AD)  contains  regulations  of  forced  cultivation of  pepper,  the  pepper  trading  regulations,  and  also  contains  civil and criminal  laws. On the other hand, this inscription  also reveals a   pattern   of   Jakarta-Lampung    relationship   in   the   seventeenth century:  in terms of political,  economic,  social and cultural  rights.